Analysis of the Marketing Strategy for Iron Crafts in an Effort to Increase Welding Workshop Income in Sanggrahan Hamlet, Bendungan Village - Vicki Dwi Purnomo (Formosa Journal of Science and Technology, 2023)
This study aims to find out how the marketing strategy is used in an effort to increase the income of welding workshops in the Sanggrahan Environment.  This research is a type of qualitative descriptive research.  Data collection techniques used are observation, interviews.  Data analysis used descriptive qualitative analysis.  It was concluded that the marketing strategy implemented by the welding shop for iron products was to maintain product quality, provide price discounts, strategic locations for welding workshops and promote products by means of personal selling, giving business cards and finally promotion through the Facebook group.  Because he always prioritizes product quality, has the principle of honesty, and does not make a habit of swearing when trading and always pays attention to buying and selling contracts.  This can happen because it is supported by several factors that can trigger an increase in the income of the welding shop, welding must pay attention to operational conditions both in terms of marketing strategy and recruiting professional employees.